2008
DOI: 10.1128/cvi.00117-08
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of New Formalin-Detoxified Botulinum Neurotoxin Toxoids

Abstract: Antigenicities of several formalin-detoxified botulinum neurotoxin preparations were measured by inhibition and sandwich enzyme-linked immunosorbent assay (ELISA), and immunogenicity was studied in mice. The toxoids were derived primarily from the serotype A 150-kDa neurotoxin protein, while one toxoid was derived from the naturally occurring 900-kDa toxin-hemagglutinin complex. Antigenicity was severely compromised in two commercially available toxoids. A variety of new toxoids were synthesized in-house by op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…These results were consistent with previous studies, especially when the vaccine or immunogen used was a commercial immunogen; native immunogen reported to be more immunogenic than those of the commercial toxoid (Witcome et al, 1999;Keller, 2008). In the present study, immunogen used was a commercial C. botulinum toxoid.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…These results were consistent with previous studies, especially when the vaccine or immunogen used was a commercial immunogen; native immunogen reported to be more immunogenic than those of the commercial toxoid (Witcome et al, 1999;Keller, 2008). In the present study, immunogen used was a commercial C. botulinum toxoid.…”
Section: Resultssupporting
confidence: 93%
“…These considerations have led the researchers to develop a more practical method of testing by applying the principles of immunodiagnostics such as ELISA. Lee et al (2005), Atassi (2006), and Keller (2008) suggested that if immunodiagnostics need to be developed, it would be better if using antibodies produced from modified C. botulinumintact toxin. They found that "home-made vaccine" from native C. botulinum antigens were more immunogenic and more protective than those of commercial antigens (Keller, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our low immune responses and resulting mediochre limits of detection for serotype E and F especially, would indicate that using newer more native toxoided formulations [63], [64], catalytically inactive mutants [65], [66], [67], bead bound forms [56] or recombinant BoNT fragments [14], [18], [68], [69] may deliver a wider diversity of sdAb with higher sensitivities. To our knowledge, these sdAb represent the first recombinant antibodies specific for BoNT serotypes other than A, B or E [70], [71], [72], [73] and we hope these and future improved derivatives will facilitate increased biosecurity.…”
Section: Resultsmentioning
confidence: 99%